(untitled) (Zaporizhzhia Historical Review, 2021)
New parties appear in the second part of the 90-th. Most of them donít have ideological orientations. We mean, first of all SDPU(O) and Party of Regions. Analyzing the demographical processes in Ukraine, the dynamics of numerous parties and the results of elections to the Supreme Rada and of referendum in 2000, the author puts forward the hypothesis of political partyís creation by illusion of considerable electoral support. It is assumed that the basis of the given method of party formation is the possibility of administrative impact of certain political forces